Managing intra-operative complications during totally extraperitoneal repair of inguinal hernia - Lomanto Davide; Katara Avinash (Journal of Minimal Access Surgery, 2006)
Laparoscopic inguinal hernia repairs are looked upon as technically demanding procedures having have a stiff ′learning curve′ associated with its performance in terms of clinical outcome and patient′s satisfaction. Complication rates have been shown to drop with increased surgical experience. The complication rate for laparoscopic repair of inguinal hernia ranges from less than 3% to as high as 20%. Complications of a totally extraperitoneal (TEP) repair include general complications that occur with any surgical procedure and anesthesia, mesh-related complications and those specific to the TEP procedure, like visceral injury, vascular injury, nerve injury and injury to the cord. Intraoperative complications can occur at every step of the operation, even though some of them are only occasionally reported. However, it is important to analyze all of them chronologically, so that we can define methods to prevent them or tackle them if they occur. Risk reduction strategies are required to improve the clinical outcome of TEP and this must be adopted for each individual surgical step.